The relative age effect is larger in Italian soccer top-level youth categories and smaller in Serie A - Brustio, P. R.; Lupo, C.; Ungureanu, A. N.; Frati, R.; Rainoldi, A.; Boccia, G. (PLOS ONE, 2018)
The relative age effect (RAE; i.e., an asymmetry in the birth distribution) is a bias observed in sport competitions that may favour relatively older athletes in talent identification. Therefore, the aim of this study was to investigate the presence of RAE in elite soccer players competing in the Italian championships, even considering the discriminations of younger and older Serie A players (in relation to the median age of the sample), and different positional roles (i.e., goalkeeper, defender, midfielder, forward) for each observed category. A total of 2051 players competing into the 2017-2018 Italian under-15 (n = 265), under-16 (n = 362), under-17 (n = 403), Primavera (n = 421) and Serie A (n = 600) championships were analysed. The birth-date distributions, grouped in four quartiles (i.e., January-March, Q1; April-June, Q2; July-September, Q3; October-December, Q4), were compared to a uniform distribution using Chi-squared analysis. The week of birth was analysed using Poisson regression. The results showed a large over-representation of players born in Q1 in all soccer player categories. However, the effect size of this trend resulted smaller as age increased. Individuals born in Q1 have about two-folds more chances to become a Serie A player compared to those born in Q4. The Poisson regression analysis showed that RAE was greater for defenders than for forwards among all categories. Therefore, a strongly biased selection emerged among elite soccer players competing in Italian championships, highlighting how young individuals born in the first three months have many more chances to become elite players compared to the others.